THE EFFECT OF SCIENTIFIC THINKING ABILITIES IN SCIENCE LITERACY ON STUDENTS' LEARNING OUTCOMES IN THE SCIENCE PLANTS LESSON IN GRADE IV SDN 012 UJUNGBATU: PENGARUH KEMAMPUAN BERPIKIR ILMIAH DALAM LITERASI SAINS TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN TUMBUHAN IPA KELAS IV SDN 012 UJUNGBATU - Desva Wahyuni Safitri; Laili Rahmi (SOSIOEDUKASI, 2025)
This study aims to examine the influence of scientific thinking ability in science literacy on students’ learning outcomes in the topic of plants within the Natural Sciences subject for Grade IV at SDN 012 Ujungbatu. Employing a quantitative approach with a correlational method, the research involved all 28 students in the class using a saturated sampling technique. Instruments used included a Guttman scale questionnaire to assess scientific thinking ability and multiple-choice tests to evaluate learning outcomes. Validity and reliability tests were conducted using SPSS version 25, with all items meeting the standards (Cronbach’s Alpha = 0.920 for the thinking skills questionnaire and 0.960 for the learning test). Item analysis revealed balanced levels of difficulty and good discriminating power. Prerequisite tests showed that the data met the assumptions of normality and homogeneity. The hypothesis test using linear regression analysis demonstrated a significant positive effect of scientific thinking ability on science learning outcomes, with a regression coefficient of 0.450 and a significance level of 0.000. The findings confirm that students with higher scientific thinking abilities tend to achieve better academic results. Therefore, fostering scientific thinking skills in the context of science literacy is essential to enhance students' academic performance and critical reasoning from an early age.